2013
DOI: 10.1097/ico.0b013e3182632c07
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Corneal Sensation and Ocular Surface in Patients With Asymmetrical Keratoconus

Abstract: The corneal sensitivity and ocular surface changes were significant in the subclinical KC and KC eyes compared with the control subjects. Ocular surface disease in KC was characterized by tear deficiency disorder and abnormal impression cytology results. However, no significant difference in tear osmolarity was found among the groups. The decrease in corneal sensitivity and ocular surface change may be associated with the pathogenesis of ocular surface changes in KC and the progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…So, the low levels of the corneal sensitivity in some of our patients on preoperative period can be explained with these findings. 21 Mocan et al and Ozgurhan et al were also reported the similar mean corneal sensitivity range with our study at the patients with keratoconus that have decreased the subbasal nerve fiber density. [20][21][22] Mastropasqua et al 23 reported the traditional CXL-induced marked corneal modifications, which were poorly evident in the transepithelial method.…”
Section: Discussionsupporting
confidence: 89%
“…So, the low levels of the corneal sensitivity in some of our patients on preoperative period can be explained with these findings. 21 Mocan et al and Ozgurhan et al were also reported the similar mean corneal sensitivity range with our study at the patients with keratoconus that have decreased the subbasal nerve fiber density. [20][21][22] Mastropasqua et al 23 reported the traditional CXL-induced marked corneal modifications, which were poorly evident in the transepithelial method.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed a reduction in goblet cell density in KC patients, confirming results of several previous studies. 3,37,38 Furthermore, KC goblet cells produced less mucin, i.e. a lower CLT, thus secreting less mucin into the tears, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…12 Indeed, keratoconic eyes have a damaged ocular surface suffering from the consequences of inadequate tear and mucin production, as well as aberrant antioxidant status and proteome alterations that affect tear fluid stability and quality. [93][94][95][96][97] Thus, the affected ocular M A N U S C R I P T…”
Section: Inflammatory Mediators In Tear Fluid Of Patients With Kmentioning
confidence: 99%